The origin of the Karakhanid dynasty and the founding tribes of the Khaganate (Journal of history, 2022)
This article provides a detailed scientific study of the political history and geographical location of the Karluks, Oguzes, Chigils, Yagma, Tukhsi and other tribes that founded the Karakhanid state in Maurennahr, Semirechye and some parts of East Turkestan. In particular, the article deals with issues of origin, including the tribal origin of the Karakhanid dynasty, their scientific analysis is carried out on the basis of a number of sources, and an assessment is made of many views on the formation of this dynasty. And also, in a historical and geographical way, the works of medieval authors about historical events in the Central Tien Shan and its environs are reviewed, which describe the role of the Uyghurs, who destroyed the East Turkestan Khaganate with the help of the Karluks, Kyrgyz and other tribes, or about the Karluk tribe, who migrated south after them. victory. In addition, the article scientifically refutes the assertions of a number of researchers that the Karakhanid rulers descended from the Uighurs, Karluks, Tukhsi, Turkeshs or Yaghmas, based on erroneous information from Eastern authors, and analyzes the concept of founding the Karakhanid dynasty by the Chigil tribes based on various source materials.